The Relationship Between Oral Bacterial Biofilm: A New Approach To Dental Caries Prevention - Ghazal , Sabreen G.; Qbaid , Khmaeel; Hashim , Hanan Saad (American Journal of Biology and Natural Sciences, 2026)
Dental caries remains one of the most prevalent chronic diseases worldwide, primarily driven by biofilm-forming bacteria such as Streptococcus mutans. These microorganisms exhibit strong resistance to conventional antimicrobial agents due to their capacity to form complex biofilm matrices, which hinder antibiotic penetration and promote horizontal gene transfer of resistance traits. Recent advances in nanotechnology have introduced titanium dioxide nanoparticles (TiO₂NPs) as promising antimicrobial agents with unique physicochemical properties, including high surface-to-volume ratio, photo catalytic activity, and the ability to generate reactive oxygen species (ROS). This study investigates the antimicrobial potential of TiO₂NPs against bacterial isolates from human dental caries. Characterization of the synthesized TiO₂NPs was performed using field emission scanning electron microscopy (FE-SEM) and X-ray diffraction (XRD), confirming Nano scale crystalline structures with average particle sizes between 42–50 nm. Experimental findings demonstrated that TiO₂NPs significantly inhibited bacterial growth and disrupted biofilm formation through ROS-mediated membrane damage, protein and DNA degradation, and interference with extracellular polymeric substance (EPS) synthesis. Furthermore, TiO₂NPs treatment reduced acidogenicity within the biofilm microenvironment, mitigating enamel demineralization. These results highlight TiO₂NPs as an effective nanomaterial with considerable potential for dental applications, including antimicrobial coatings and preventive strategies against biofilm-associated oral diseases.